2004
DOI: 10.1002/jsfa.1806
|View full text |Cite
|
Sign up to set email alerts
|

Development of biodegradable coatings for covered horizontal bunker‐stored silage

Abstract: The addition of different plasticizers, thickeners and hydrophobic compounds such as fatty acids in biodegradable coatings has been evaluated using pH values and dry matter content as criteria in silage during one month of storage at room temperature under laboratory conditions. A base coating solution was prepared with whey protein concentrate, calcium caseinate and carboxymethylcellulose. From the base coating solution, derivative coating solutions were developed to evaluate the effect of plasticizers by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Self-heating of silages in silos may suggest that the biodegradable layer failed to protect the silages from spoilage when they were exposed to atmospheric influences. Denoncourt et al (2004b) reported that production of good silage using biodegradable film is dependent on plastic components. In fact, a number of components characterized by different mechanical and physical properties give specific functional properties to the film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-heating of silages in silos may suggest that the biodegradable layer failed to protect the silages from spoilage when they were exposed to atmospheric influences. Denoncourt et al (2004b) reported that production of good silage using biodegradable film is dependent on plastic components. In fact, a number of components characterized by different mechanical and physical properties give specific functional properties to the film.…”
Section: Resultsmentioning
confidence: 99%
“…However, the management of worn-out polyethylene films is a problem. Alarmingly, worn-out silage wrap is going to illegal dumping sites, being buried or burned, while the released components of polymer plastics are a serious environmental threat (Rymarz and Klecan, 2001;Majdiuk, 2002;Rutkowska et al, 2002;Denoncourt et al, 2004aDenoncourt et al, , 2004bŚwiątkowski and Walczak, 2004;Borreani and Tabacco, 2005;Laffin et al, 2005;Denoncourt et al, 2006Denoncourt et al, , 2007Borreani et al, 2014;Borreani and Tabacco, 2015). One alternative to standard coating is biodegradable film produced on the basis of natural origin polymers (chitosan, cellulose, starch, soy or whey protein, and others) or synthetic macromolecular compounds that provide food for microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation